Selected aspects of psychological flexibility and experiencing the occupational burnout syndrome among speech therapists - Guzy, Anna (Logopedia Silesiana, 2021)
In this article, the author examines the relationship between selected aspects of psychological flexibility and the experience of the burnout syndrome among professionally active speech therapists. The author presents results from a correlation analysis (n = 143) of the relationship between the burnout syndrome (OLBI) and selected aspects of psychological flexibility: experience avoidance (MEAQ-30), cognitive fusion (CFQ), and acceptance and action (AAQ-II). These results indicate that there is a statistically significant relationship (p < 0.05) between burnout and non-acceptance and action (0.38), cognitive fusion (0.56), as well as the following components of avoidance (0.4): procrastination (0.37), repression/denial (0.33) and the resistance to stress (–0.26). The conclusions emphasize the need to carry out burnout prevention therapy among speech therapists which should involve instruction on the skills that make up the different aspects of psychological flexibility.